TEKNIK KONSERVASI TANAH LAHAN KERING UNTUK MENGATASI DEGRADASI LAHAN PADA DESA MOJOREJO, LAMONGAN - Deddy Erfandi (Bumi Lestari Journal of Environment, 2013)
AbstractSoil conservation is one important aspect in supporting food security program. It is necessary tocreate an area that has a sustainable environment. Mojorejo Village, District Modo, Lamongan,East Java, has an area of ± 1,406 ha. Most of the area is dry land agro-ecosystem includingupland lowland dry climate. Topography is undulating to hilly with deep and rocky limestonesolum. In creating a sustainable environment, research has been conducted in the village onsystem conditions of dryland soil conservation techniques to address land degradation. Thestudy aims to look at the soil conservation and soil conservation technologies recommended insitu, in order to address land degradation. Observations suitability for some commodities showthat land can be developed for agricultural commodities in the village square Mojorejo 878.02ha (92.56%), while the remaining area of 70.54 ha (7.22 %) could not be developed foragriculture because of the form settlement and land biophysical conditions do not allow. Thereis a potential source of water to irrigate rice fields allowed. On mixed farms that have slopes of8-15%, the maximum proportion of annual crops is 50 % with a permanent stone terracing,while mixed farms on the slopes of 15-25%, the maximum proportion of annual crops is 30% witha permanent stone bench terraces.